Analytical solution to predict performance and optimum design parameters of a constructal T-shaped fin with simultaneous heat and mass transfer. (1st May 2015) - Hazarika, Saheera Azmi; Bhanja, Dipankar; Nath, Sujit; Kundu, Balaram
Abstract: The present article establishes an analytical method for predicting the performance of a fully wet constructal T-shaped fin assembly under dehumidifying conditions. The temperature and humidity ratio differences are the driving forces for heat and mass transfer, respectively. The mass transfer process is calculated by adopting the humidity ratio as a polynomial function with fin surface temperature, which is determined from the psychrometric correlation using regression analysis. Considering this, the governing equation of the fin assembly becomes nonlinear. A solution methodology, namely Adomian decomposition method is adopted to determine the temperature field in both the stem and flange part of the T-shaped fin. The thermal performance and optimization analysis of the fin has been carried out for a wide range of thermo-psychometric and geometric parameters. For validation of the present analysis, a numerical scheme called finite difference method has been employed on the same problem. Further a comparative study has also been presented between the present work and published work to show the variation in fin performances due to mass transfer and a reasonable difference in results has been noticed. Highlights: Constructal T-shaped fin assembly under dehumidifying conditions is proposed. Fully wet condition of the fin is considered for the analysis. Adomian decomposition method is adopted to determine the temperature field. Thermal performance and optimization analysis of the fin has been carried out. Fin performances decrease with the increase in relative humidity and Biot number.